A cost-effective and efficient strategy for Illumina sequencing of fungal communities: A case study of beech endophytes identified elevation as main explanatory factor for diversity and community composition. (April 2016) - Siddique, A.B.; Unterseher, M.
Abstract: We describe an accurate and efficient workflow for highly multiplexed paired-end Illumina sequencing of fungal full-length ITS amplicons. The impact of habitat and substratum conditions on leaf-inhabiting fungal communities was analysed. Fully vital and clearly senescent leaves of European beech ( Fagus sylvatica ) were sampled along an elevation gradient of about 1000 m in the Bavarian Alps, Germany, in autumn 2013. Surface-sterilised leaves were used for genomic DNA extraction, tagging-by-amplification and high-throughput sequencing. Significant correlation of community composition with elevation was observed. The mycobiome was little affected by the physiological state of the leaves, because only a partial shift of taxonomic composition was observed from vital towards clearly senescent leaves.